Clearance of Chronic Actinic Dermatitis With Dupilumab Therapy in Chinese Patients: A Case Series - Ali, Kamran; Wu, Liming; Lou, HaiYue; Zhong, Jianbo; Qiu, YunMi; Da, JiaYang; Shan, JingPeng; Lu, KaiNing (Frontiers in Medicine, 2022)
Chronic actinic dermatitis (CAD) is a rare chronic immunological photo-dermatosis resulting in pruritic eczematous eruption on sun-exposed skin to ultraviolet (UV) light. The disease mechanism may include a delay-type hypersensitivity reaction to an endogenous photo-induced antigen, postulated to be UVR-altered DNA, but the exact pathophysiology is unknown. Minimum erythema dosing and patch testing are diagnostic tools of CAD. There are limited safe and effective treatment options for CAD. Herein, a case series of three patients with severe recalcitrant CAD is presented after being treated with dupilumab off-label. The patients in this study had persistent severe disease and took the first-line management plan, which consists of topical calcineurin inhibitors (TCI), topical corticosteroids (TCS), and strict photoprotection. However, the above treatment options were not able to control the symptoms. The patients were treated with dupilumab 600 mg first dose, 300 mg biweekly subcutaneously (SC), and hydroxychloroquine. Dupilumab showed excellent clinical benefits, included safe and well-tolerated in chronic actinic dermatitis. Further studies are required to be carried out before being applied in clinical practice.